Virtue and Responsibility in Policy Research and Advice - Tholen, Berry (Springer International Publishing, 2018)
This book argues that ethical judgment by individual scientific policy advisors is more important than is often acknowledged. While many scientific policy advisors routinely present themselves as neutral or value free scientists, here is demonstrated that the ideal of scientific integrity as neutrality is misguided and that an alternative understanding is demanded. The book provides an overview of the type of social and political value decisions that have to be made in all phases of research and advice. It moves on to examine proposed procedures or guidelines for scientists and critically assesses plans for the democratization of decision making in science and scientific advice. The book offers a reflection on the practice of scientific advice that will appeal to practitioners and scholars of Public Administration, Public Management and Policy Analysis. "Dr. Tholen has brilliantly zeroed in on the difference between value-driven inquiry and pseudo-science, and what he reveals is critical in distinguishing facts from falsehoods, the importance of which cannot be over-estimated in the post-truth era." -Carole L. Jurkiewicz, University of Massachusetts Boston, USA "This highly thought-provoking book presents a compelling argument that a scientific advisor should try to be both a good scientist and a responsible citizen. It offers invaluable counsel for finding a rational and responsible role for scientific advisors." -Tony Bovaird, University of Birmingham, UK.